1982
DOI: 10.1111/j.1471-0528.1982.tb04630.x
|View full text |Cite
|
Sign up to set email alerts
|

Feto‐maternal consequences of high‐dose glucose infusion during labour

Abstract: The effects on the fetus of high doses of glucose given to the mother in labour to correct maternal ketonuria were investigated. Three groups of patients were compared: one group received 1 litre of 10% (wiv) glucose intravenously over 1 h, the second group received 1 litre of 0.9% sodium chloride solution intravenously over 1 h and the final group had no supplementary infusion. It was observed that whereas glucose administration rapidly corrected maternal ketonaemia, there was a significant fall in p H and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 15 publications
2
24
0
2
Order By: Relevance
“…Steroid administration might induce maternal hyperglycemia, especially in women with gestational diabetes (GDM) or pre-existing diabetes mellitus (DM). The optimal maternal glycemic control is necessary during ACS treatment in pregnancies with GDM as well as DM because maternal hyperglycemia is associated with fetal acidosis [3,4]. Several authors have demonstrated maternal glycemic control after the corticosteTime-dependent changes in insulin requirement for maternal glycemic control during antenatal corticosteroid therapy in women with gestational diabetes: a retrospective study [5][6][7][8][9].…”
mentioning
confidence: 99%
“…Steroid administration might induce maternal hyperglycemia, especially in women with gestational diabetes (GDM) or pre-existing diabetes mellitus (DM). The optimal maternal glycemic control is necessary during ACS treatment in pregnancies with GDM as well as DM because maternal hyperglycemia is associated with fetal acidosis [3,4]. Several authors have demonstrated maternal glycemic control after the corticosteTime-dependent changes in insulin requirement for maternal glycemic control during antenatal corticosteroid therapy in women with gestational diabetes: a retrospective study [5][6][7][8][9].…”
mentioning
confidence: 99%
“…Indeed, in some cases, maternal glucose concentrations decline [3].To prevent or treat ketosis and to supplement glucose, glucose can be administered intravenously. When, however, high concentrations are administered, maternal and fetal hyperglycemia may occur, which, subsequently, may lead to an increase in both maternal and fetal lactate levels resulting in a metabolic acidosis [6,13,14]. In addition, hyperglycemia results in a higher fetal oxygen consumption, resulting in a higher oxygen debt, which further increases the risk of acidosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous glucose administration during labor has been associated with fetal metabolic acidosis [6,13,14,19]. Regarding the effects of eating and drinking on maternal and fetal metabolism during labor, hardly any data are available.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal metabolic acidosis was observed after a rapid infusion of 100 g glucose per hour [28,36]. Fetal metabolic acidosis was observed after a rapid infusion of 100 g glucose per hour [28,36].…”
Section: Glucose Administrationmentioning
confidence: 99%